Condotel Di Pekanbaru Dengan Pendekatan Arsitektur Modern - Aussuarli, Romi; Hidayat, Wahyu; S, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Pekanbaru was chosen as the best investment destination, it is evident from the current real condition with the rapid growth of economy and investment. As a metropolitan city based onbusiness activities, the potential investment in residential business such as Condotel is very promising. Condotel can function as condominium and hotel, from condotel ownership aspect canbe owned by individual, the owner can occupy the unit with the specified time, when the owner does not occupy the unit, the unit can be rented like hotel and managed by the hotel management. In the design of Condotel, the design approach that is applied prioritizes the principles of designing Modern Architecture with the goal of the purpose that the building is designed to follow the trend in accordance with the times. This can be seen from the form of its simple building mass, clean, functional, stylish, up-to-date, related to the modern lifestyle that is growing rapidly today. So with the Condotel in Pekanbaru can help the need for shelter for migrants or businessmen.Keywords: Condotel (Condominium Hotel), Modern Architecture